The Characteristics of Copper Containing SBA-15 Prepared by Impregnation and pH Adjustment Methods and Their Activities For N2O Decomposition - Mohd Haizal, Mohd Husin; Dewayanto, Nugroho; Mohd Ridzuan, Nordin; Li, Jinlin (AENSI, 2015)
Two types of Cu-SBA-15 catalysts were successfully prepared by impregnation and by pH adjustment methods. All synthesized materials have been characterized by XRD, Nitrogen adsorption–desorption, and TEM. After the impregnation of copper, the unitcell, specific surface area and pore volume of SBA-15 werefoundto decrease, while the formation of CuO deposited on the framework was detected. On the contrary, the catalyst prepared by pH modification method indicated the increase of unit-cell, surface area, pore volume, and wall thickness after the incorporation of the copper ions on SBA-15 and copper atomswere substituted into the framework of the SBA-15. Series of N2O decomposition experiments were carried out using the catalysts. Cu/SBA-15 samples prepared by pH adjustment method showedhigher catalytic activity thanCuSBA-15 samples prepared by impregnation method.